Motivational Factors of Online Learning in Higher Education - Haasio, Ari; Kannasto, Elisa (European Journal of Applied Sciences, 2024)
Among others, universities were forced to modify their operation when the global pandemic hit in 2020. Teachers and students worldwide were forced to move online to continue learning after several lockdown orders. This study focuses on a Finnish University of Applied Sciences where an extensive survey was sent to all students a year after their student life had changed completely. Qualitative content analysis was done to analyze survey responses from 619 students from different fields and study backgrounds. The results indicate that several motivational factors around online learning are also related to things other than technology or pedagogical choices. The factors encouraging or discouraging motivation are divided into five categories: 1) Life situation, 2) Previous experience, 3) Social relationships, 4) Technology and internet skills and attitude, and 5) Financial resources. The proposed model of motivation factors related to online learning includes: 1) Environmental, 2) Individual, and 3) Pedagogical factors.